FACTORS INFLUENCING THE OCCURRENCE OF TYFOID FEVER INSULTAN ISKANDAR MUDA HOSPITAL, NAGAN RAYA DISTRICT 2022 - Suci Harianti; M. Iqbal Fahlevi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Typhoid fever is a disease caused by Salmonella Typhi which is usually spread by consuming contaminated food or water. Cases of typhoid fever every year around the world reach 21 million cases and 128,000 to 161,000 deaths that occur each year. The research objective was to find a relationship between the independent variables and the dependent variable, which was intended to find a relationship between the factors that influence the occurrence of typhoid fever at Sultan Iskandar Muda Hospital, Nagan Raya Regency. The type of research used in this study was quantitative research. By using a cross sectional approach. The research was conducted at the Sultan Iskandar Muda Hospital in November 2022. The sample taken in this study was 60 out of 95 respondents. The sampling technique for this study was carried out using Simple Random Sampling. Based on the test, there was a relationship between gender (p=0.000), the relationship between eating habits outside (p=0.001), food processing at home (P=0.000), the relationship between waste management (0.000 ), there was no relationship between hand washing habits (p=0.789), no age relationship (0.195) to the occurrence of typhoid fever at Sultan Iskandar Muda Hospital. From these results it can be concluded that washing hands before eating and age do not affect typhoid fever while gender, eating habits outside the home, food processing at home, waste management have an influence relationship between waste management (0.000), no relationship between hand washing habits (p=0.789), no relationship between age (0.195) and the occurrence of typhoid fever at Sultan Iskandar Muda Hospital. From these results it can be concluded that washing hands before eating and age do not affect typhoid fever while gender, eating habits outside the home, food processing at home, waste management have an influence relationship between waste management (0.000), no relationship between hand washing habits (p=0.789), no relationship between age (0.195) and the occurrence of typhoid fever at Sultan Iskandar Muda Hospital. From these results it can be concluded that washing hands before eating and age do not affect typhoid fever while gender, eating habits outside the home, food processing at home, waste management have an influence